2023
DOI: 10.1038/s41598-023-33075-5
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of N-doping activated carbons from fish waste and sawdust for Acid Yellow 36 dye removal from an aquatic environment

Abstract: Acid Yellow 36 (AY36) dye is a synthetic azo dye that is excessively used in various industries, causing hazardous environmental effects. The main target of this study is the preparation of self-N-doped porous activated carbon (NDAC) and the investigation in eliminating the AY36 dye from the water solution. The NDAC was prepared by mixing fish waste (60% protein content) which was considered a self-nitrogen dopant. A combination of Fish waste, sawdust, zinc chloride and urea with a mass ratio (5:5:5:1) was sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 118 publications
1
5
0
Order By: Relevance
“…From the values of B and A (Table 5 ) we can deduce that physical adsorption occurred. These results are in agreement with El-Nemr et al 35 who reported that, the adsorption data were defined well by LIM and TIM where the optimum pH value of Acid yellow 36 dye removal was 1.5, with a removal efficiency of 85.86%.
Figure 14 ( a ) Linearized LIM, ( b ) Linearized FIM, ( c ) Linearized TIM, ( d ) Linearized HIM, ( e ) Linearized DRIM of Cr 6+ ions of 100–400 mg/L initial concentration and 1.0 g/L NDAC600 dose at 25 ± 2 °C.
…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…From the values of B and A (Table 5 ) we can deduce that physical adsorption occurred. These results are in agreement with El-Nemr et al 35 who reported that, the adsorption data were defined well by LIM and TIM where the optimum pH value of Acid yellow 36 dye removal was 1.5, with a removal efficiency of 85.86%.
Figure 14 ( a ) Linearized LIM, ( b ) Linearized FIM, ( c ) Linearized TIM, ( d ) Linearized HIM, ( e ) Linearized DRIM of Cr 6+ ions of 100–400 mg/L initial concentration and 1.0 g/L NDAC600 dose at 25 ± 2 °C.
…”
Section: Resultssupporting
confidence: 92%
“…The XRD spectra of all nitrogen-doped activated carbons reflect two peaks around 24.635° and 43.558° assigned to the (002) and (101) plans of carbons, respectively. In this case, the weak intensity peak would reveal the smaller crystallites, which is convenient with the amorphous structure of NDACs 35 , 36 .
Figure 6 XRD analysis of ( a ) NDAC600, ( b ) NDAC700, ( c ) NDAC800.
…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Different methods are used to effectively remove heavy metal ions and dyestuffs from water sources. Examples of these are ion exchange, photocatalysis, coagulation, photodegradation, biological treatment, chemical oxidation/reduction, reverse osmosis and ultrafiltration 24 28 . These methods have some disadvantages such as high cost, less efficiency, other waste products and so on.…”
Section: Introductionmentioning
confidence: 99%